Compact Carpenter Ant (proposed common name), Camponotus planatus (Roger) (Insecta: Hymenoptera: Formicidae) - John Warner; Rudolf H. Scheffrahn (EDIS)
The compact carpenter ant, Camponotus planatus (Roger), although primarily an arboreal species, is increasingly becoming recognized as a structural pest in Florida. This common name is still unofficial. A smaller, more "compact" and close relative of the Florida carpenter ant complex (Camponotus floridanus and C. tortuganus) and often found living in close proximity with them, the compact carpenter ant is the subject of numerous inquiries to pest control operators in the South Florida area. This document is EENY-189, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2001.